Gamelan Pelegongan Sakral Di Pura Prajurit Desa Adat Pagan Kelod - Sandiawan, I Kadek Deo (Jayapangus Press, 2021)
Gamelan pelegongan is a musical instrument that originates from Bali. If you look at the instrumental form of the song types which show characteristics of authenticity, then you can be sure that the gamelan pelegongan is not included in the group of ancient gamelans (old gamelan) in Bali. The pelegongan gamelan only came into existence after the existence of the semar pegulingan gamelan which had a seven-tone pelog tune. Gambelan pelegongan is one of the Balinese gamelan barungans which was usually used to accompany the palace legong dance during the kingdoms. This barungan unit consists of a number of tools which have their own names and functions for the complete unity of the barungan. In the Ajigurnita lontar, gamelan pelegongan is said to be in the same family or similar to gamelan bebarongan, gamelan joged pingitan, and gamelan semar pegulingan which does not have selendro notes like semar pegulingan. In accordance with the specific form of each gamelan barungan in Bali, the songs from each type of gamelan also have different compositions and are typical forms of each type of gamelan. The sacred Pelegongan gamelan in the warrior temple is very ancient, because the gamelan existed in 1932, and what makes the proof of the gamelan is the year located on the gamelan plaque, specifically on the Gong instrument. This gamelan can be worn or used when performing Odalan at the warrior temple, because the pelegongan gamelan that is there is only specific to that temple and accompanies the legong or sesuhunan legong dance found at the warrior temple in the pagan kelod village. This research aims to enable young artists to know about the existence of the pelegongan gamelan found in the warrior temple. As we know, this sacred gamelan can only be performed during the Legong dance at the temple. And for several years this gamelan has also been used for cultural performances, so that the pelegongan gamelan is not damaged, what makes it sacred is that it has its own characteristics and also has a style or style of pelegongan gending and legong dance.